2018
DOI: 10.3389/fpsyg.2018.00565
|View full text |Cite
|
Sign up to set email alerts
|

Brain Training in Children and Adolescents: Is It Scientifically Valid?

Abstract: Background: Brain training products are becoming increasingly popular for children and adolescents. Despite the marketing aimed at their use in the general population, these products may provide more benefits for specific neurologically impaired populations. A review of Brain Training (BT) products analyzing their efficacy while considering the methodological limitations of supporting research is required for practical applications.Method: searches were made of the PubMed database (until March 2017) for studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 106 publications
(230 reference statements)
1
17
0
Order By: Relevance
“…Cicerone and colleagues 70 suggested that more complex metacognitive abilities (e.g., cognitive self-monitoring, emotional self-appraisal, and imagined use of strategies in real situations) should be stimulated in pediatric ABI to generate CCT effects on everyday functioning. This would explain why numerous studies found no generalization effects of CCT programs, questioning their usefulness with respect to adjustment in ecological settings [71][72][73] .…”
Section: Discussionmentioning
confidence: 99%
“…Cicerone and colleagues 70 suggested that more complex metacognitive abilities (e.g., cognitive self-monitoring, emotional self-appraisal, and imagined use of strategies in real situations) should be stimulated in pediatric ABI to generate CCT effects on everyday functioning. This would explain why numerous studies found no generalization effects of CCT programs, questioning their usefulness with respect to adjustment in ecological settings [71][72][73] .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is important for future strategy-based training designs to consider child developmental factors. In our view, this approach can overcome the limitations of previous cognitive training designs in attention and EF, in terms of generalization and long-term effects (Rossignoli-Palomeque et al, 2018). Thirdly, this analysis has helped to clarify the relevance of instructional comprehension and self-instruction as compensatory strategies.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the limitations of process-based training have been found in the far transfer or generalization of the training in the user’s everyday life. Similarly, limitations have been found in long-term effects (Rossignoli-Palomeque et al, 2018). The aim of EF training should be the generalization of the training in children’s daily life, in cognitive skills, academic performance, and social adjustment, which are considered “far transfer.” A significant number of previous studies on EF training efficacy fail to find or examine these types of transfer results (Rossignoli-Palomeque et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…While research investigating the impact of Cogmed in brain injuries supports improvements in similar tasks as those in Cogmed training, other results are inconclusive. [ 71 ]. Hence, further research investigating the efficacy of Cogmed in improving performance in similar tasks as well as generalizability to other functional outcomes is required.…”
Section: Introductionmentioning
confidence: 99%